Connecting Emotionally: Examining the Impact of Narrative Video Advertising on Consumer Involvement and Brand Attachment - Rahimah, Anni; Aqfa Dzikrullah, Shannon Saghava; Astira, Ameylia Ayu (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2025)
The increasingly competitive advertising landscape necessitates innovative strategies to engage potential customers effectively. This study investigates the impact of emotional and narrative-driven video advertisements on attitudes toward advertisements and advertisement involvement, ultimately fostering emotional brand attachment among viewers. This research adopts a quantitative approach, employing Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS 4 software. Data were collected through a structured survey involving 131 respondents who had utilized the GoSend service in DKI Jakarta, Indonesia. The results demonstrate that emotional and narrative elements in video advertisements exert a significant positive influence on viewers’ attitudes toward advertisements and their involvement with them. These factors contribute to developing a robust emotional attachment to the brand. Based in the SEM-PLS analysis described in the file, the strongest relationship was found between advertisement involvement and emotional brand attachment that indicating the higher one’s involvement with advertisements, the more likely they are to develop an emotional attachment to the brand. Meanwhile, a relatively weaker relationship was found between feeling-based advertising and attitude toward advertisement, compared to narrative advertising which had a stronger influence on attitude indicating that the use of narrative elements in advertisements is more effective in shaping positive attitudes than emotion-based approaches alone, although both still have a significant influence in this research model. This study contributes to the literature by examining the underexplored role of emotional narratives in shaping consumer behavior through video marketing. Using the Stimulus-Organism-Response (SOR) Theory as a framework, it provides insights into how gentle and emotion-driven advertising approaches can elicit favorable emotional reactions and strengthen consumer-brand relationships. The findings offer actionable guidance for marketers, particularly those targeting Gen Z consumers, by emphasizing the importance of crafting emotionally resonant and narrative-rich video content. Over time, such strategies can foster stronger consumer-brand bonds, enhancing loyalty and achieving long-term marketing objectives.